Artisanal culture in early modern Iberian and Atlantic worlds. (29th May 2019) - Sánchez, Antonio; Leitão, Henrique
Abstract : For several decades, historians have realized the limitations of analysing the historical past of science as a mere succession of theories. One of the most stimulating messages that the reinvention of the discipline has launched is that although there are obvious intellectual elements that promote the development and progress of science, there are also social, economic, and institutional aspects to consider. The history of science is no longer just a history of scientific ideas and theories, but also a history of institutions, communities, spaces, objects, and practices as well as a history of the complex interaction among all these dimensions. Accompanying this new panorama is a broad consensus among scholars to accept that major social changes have inexorably some impact on scientific practice and vice versa. This premise, now widespread, is especially relevant to the history of early modern science and the question of its roots because it has allowed the introduction of new agents and spaces previously excluded from the domain of scientific development. In other words, this enriched perspective has multiplied both the processes of knowledge construction and the arenas in which these processes were undertaken. More specifically, historical research is no longer limited to spaces traditionally linked to the construction of science; it now embraces less orthodox ones. Within this broadened field of inquiry, practical knowledge and the objects of material culture have come to occupy a central place. This special issue explores how the new directions in which the history of science has expanded have a direct impact on the study of Iberian science in the Atlantic world.